The relationship between personality traits and entrepreneurial intentions / Rahman Sadeghi Javan - Javan, Rahman Sadeghi (Research Management Institute (RMI), 2014)
This study investigates the impact of personality traits on intention to start an entrepreneurship. In order to examine personality traits, the big five model was used. The big five model consists of five dimensions: extroversion, agreeableness, conscientiousness, emotional stability, and openness to experience. Entrepreneurship consists of six dimensions: hardworking, risk-taking, self-confidence, creativity, flexibility, and tolerance of ambiguity. In order to collect data, a 47 items questionnaire was designed. Statistical population was university of Isfahan’s personnel, and sample size was 160 personnel and were selected based on the available sampling method. In order to analyse data,descriptive statistic, inferential statistics, ENTER method, and Durbin-Watson test has been used. To measure stability of questionnaires’ items, Cronbach's alpha was calculated for each variable separately. The results of this article indicate that personality traits have an impact on the tendency to entrepreneurship. Based on these results, between all personality traits, agreeableness, conscientiousness, neuroticism, and openness to experience have impacts on the tendency to entrepreneurship and these factors could explain 0/533 of entrepreneurship regression. Durbin- Watson test results also indicate that there is no selfcorrelation between independent variables. Finally, empirical suggestions have been offered for human resources managers and related professionals.